2015
DOI: 10.24123/jmb.v12i2.20
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Behavior of Investors Using Discriminant Analysis Approach

Abstract: Behavioral finance is a recent line of research that is attracting the attention of the investor.Behavioral finance has an important role in decision-making process of investors. Thepurpose of this study is to examine whether there are any differences in the decision ofinvestors in terms of demographic variables, such as marital status, gender, education level,and then it will be examined how the different criterias on financial behavioral factorsinclude: herding, heuristics, and behavioral factors are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…37 The fact that digital currency only exists in cyberspace precludes it from being utilized as payment for physical goods and services. 38,39 Money (also referred to as the "money supply") is anything that is created and commonly accepted as payment for goods or debt repayment. 40 Economists describe money as the frequently accepted (or generally accepted) medium of exchange.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The fact that digital currency only exists in cyberspace precludes it from being utilized as payment for physical goods and services. 38,39 Money (also referred to as the "money supply") is anything that is created and commonly accepted as payment for goods or debt repayment. 40 Economists describe money as the frequently accepted (or generally accepted) medium of exchange.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, they are unfit for use as a store of value or wealth. 38,39 Therefore, researchers have found that digital currencies are not the same as conventional money and cannot even replace it. This is because of the aforementioned significant variances.…”
Section: Methodsmentioning
confidence: 99%
“…Questions for depth interviews were modified from Isa et al [13] that is about general opinion on green office building investment, return from green office building investment, and reason for willingness to invest in green office building. The question of behavioral factors influencing investors' decisions making refers to the research of Lowies, Hall, and Cloete [6] and Meliza, Sadalia, and Fachrudin [5].…”
Section: Methodsmentioning
confidence: 99%
“…Investors who invest in financial assets can be influenced by behavioral factors, such as heuristic, prospects, and market [5]. Investors who invest in conventional property can also be influenced by heuristic factors [6].…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…Pada FL menjadi variabel moderasi. FL diukur dengan menggunakan pernyataan yang di adopasi dari [15] yaitu berjumlah 6 pernyataan, sedangkan variabel HD merupakan, pengukuran variabel [16] yaitu berjumlah 6 pernyataan. Pengukuran pada masing-masing variabel dillakukan dengan model pernyataan tertutup dengan menggunakan kuesioner berskala Likert 1 sampai 5.…”
Section: Metode Penelitianunclassified